2011
DOI: 10.1016/j.jacc.2011.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Results of Low-Dose Human Atrial Natriuretic Peptide Infusion in Nondialysis Patients With Chronic Kidney Disease Undergoing Coronary Artery Bypass Grafting

Abstract: In the post-operative acute stage, carperitide showed cardiorenal protective effects that prevented post-operative cardiac events and initiation of dialysis. Thus, perioperative infusion of low-dose carperitide may have a significant role in management of patients with renal dysfunction undergoing on-pump CABG. (Effectiveness of hANP for Cardiac Surgery in Patients With Moderate to Severe Preoperative Renal Dysfunction Without Dialysis [NU-HIT for CRF]; UMIN000001462).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 21 publications
3
74
1
Order By: Relevance
“…Because hANP inhibits the renin-angiotensin-aldsterone system and has a potent natriuretic effect, we have found that it can compensate for the adverse effects of cardiopulmonary bypass and can inhibit reperfusion injury, left ventricular remodeling, postoperative arrhythmia and renal dysfunction. [11][12][13][14][15][16] In an experiment study, cyclic guanosine monophosphate was increased by the administration of hANP, and myocardial protective effects were reported. 17,18) Recently, continuous intravenous administration of hANP or BNP have been performed in cardiac surgery worldwide, its cardiac and reno-protective effects have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because hANP inhibits the renin-angiotensin-aldsterone system and has a potent natriuretic effect, we have found that it can compensate for the adverse effects of cardiopulmonary bypass and can inhibit reperfusion injury, left ventricular remodeling, postoperative arrhythmia and renal dysfunction. [11][12][13][14][15][16] In an experiment study, cyclic guanosine monophosphate was increased by the administration of hANP, and myocardial protective effects were reported. 17,18) Recently, continuous intravenous administration of hANP or BNP have been performed in cardiac surgery worldwide, its cardiac and reno-protective effects have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, appropriate perioperative medical therapy should be provided to reduce postoperative complications related to cardiopulmonary bypass and other complications such as cerebral infarction and renal failure. [15][16][17] …”
Section: Discussionmentioning
confidence: 99%
“…For renoprotective purpose, human atrial natriuretic polypeptide (Carperitide) is administered continuously in most cases, irrespective of preoperative renal function. 10) If excessive hemodilution was observed, intraoperative modified ultrafiltration was liberally done. 11) Choice of repair procedure or replacement was decided based on surgeon's preference.…”
Section: Methodsmentioning
confidence: 99%